THE OBJECTIVE SIDE OF CRIME IN CRIMINAL LAW THEORY - Odilov Muhammadrashodxon Sarvarjon ugli (Scholar Express Journals, 2025)
In a historically short period, the country has formed institutional and legal foundations of legality and law and order, and created an effective national system for combating corruption. In implementing reforms in this direction, special attention was paid to the implementation of internationally recognized norms into national legislation. The existence of such problems in the current legislation as the absence of normative-legal definitions for a number of concepts related to corruption crimes, insufficient coverage of corruption acts by criminal legislation, hinders the achievement of expected results from the fight against corruption and further improvement of Uzbekistan's position in international rankings in this sphere. This article analyzes specifically the definition of the object and objective features of bribery crime, the interpretation of these concepts in our national legislation, and scholars' attitudes toward this concept
Keywords: corruption; corrupt offense; crime